Developing a Career App Based on Students' Interests and Talents to Support Career Planning - Kiki Mariah; Isnaria Rizki Hayati; Fadhila Rahman; Elni Yakub; Munawir (Ta'dib, 2025)
Career planning is a fundamental component of students’ development because it shapes their future educational and occupational pathways. In many schools, however, career planning is constrained by limited guidance services, students’ low awareness of their interests and talents, and the scarcity of accessible career information media conditions that can lead to less informed career decisions. This study addresses a gap in prior digital career media, which often provide generic information without integrating a validated interest, talent mapping process, and counselor support functions; the novelty of the proposed application lies in combining interest talent profiling with personalized career information and counselor oriented features, thereby contributing conceptually to a data-informed and personalized model of digital based career guidance. Using a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), data were collected through observations, interviews, a Student Career Media Needs Survey, and expert validations of content, design, and language. The findings indicate that the developed interest,  and talent, based career information application achieved a very valid rating in both content relevance and usability. The application enables students to explore their strengths, identify suitable career options, and access information on study programs across universities. Moreover, its digital format supports guidance counselors in identifying students’ potentials earlier and delivering more personalized career planning assistance. Overall, this application offers an effective and engaging tool for integrating technology into school based career guidance and making career exploration more meaningful, interactive, and aligned with contemporary learners’ needs.